Neuronal representation of fabric texture for thermal microenvironment - Liu Yuqing (Thermal Science, 2013)
Fabric, our second skin with moisture and thermal capacity for skin temperature regulation, can arouse feelings of pleasant and discomfort. To examine the neurocognitive ability and emotion of fabric tactile perception under different local temperatures, we used functional magnetic resonance imaging with the same denim fabric stimuli and forearm contact area, and found a functional dissociation: the affective regions was more involved during warm condition, the discriminative regions were more involved during neutral condition and the basis regions were significance during cool condition. The higher local skin temperature environment can result in the improvement of sensitivity and discriminability by dorsal pathway (spatial) and ventral pathway (frequency) for fabric perception. Our results help to explain how the brain uses internal models to interpret external fabric tactile stimuli with micro environmental changing.